Pengaruh Kinerja Keuangan Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Sektor Pertambangan - Sihombing, Erika Natasya; Wenny, Cherrya Dhia (Universitas Multi Data Palembang, 2024)
The implementation of this research aims to analyze the value of mining sector companies as influenced by company size and performance. The type of data source implemented in the research is secondary data with the number of samples used totaling 52 samples, where the sample is selected through the purposive sampling method. Furthermore, the data that has been collected will be processed with the help of SPSS 26 software. Based on the results of data analysis, it is found that the value of the company is influenced by financial performance but the size of the company does not have an influence on it.